Розробка шаблону курсового проекту у видавничій системі LATEX по СТЗВО-ХПІ-3.01-2018 - Легка, Д. К.; Азаренков, Володимир Ілліч (Харківський національний університет радіоелектроніки, 2019)
The examination of the main factors hindering the implementation of national standards and regulations for the execution of documents in the LATEX publishing system, taking all existing possibilities into account. The results of the analysis of the methods for the implementation of the regulations of the text capturing and layout of Ukrainian (Cyrillic) texts have been presented. Approaches for meeting the requirements of СТЗВО-ХПІ-3.01-2018 for executing courses at the Kharkov University "Kharkov Polytechnic Institute" in the publishing systems AMSTEX, LATEX2ε, TEXLive, LuaTEX, XƎTEX and XƎLATEX and their derivatives have been proposed.
Keywords: вищій навчальний заклад; текст; документ; видавничий пакет LATEX; верстка; редактор; текстові документи; сфера навчального процесу